Coping with Thesis Writing: An Analysis of Stress Management Techniques in Higher Education - Ardiana, Alvina Della; Soetjiningsih, Christiana Hari (Jurnal Bimbingan dan Konseling Terapan, 2024)
This research explores the relationship between Problem-Focused Coping and Academic Stress among students at Satya Wacana Christian University. In an academic environment where students face immense pressure, particularly during the thesis-writing phase, understanding how coping strategies impact stress levels is crucial. The study involves 145 students, predominantly female, from different faculties, who were surveyed using the Academic Stress Scale and Problem-Focused Coping Scale. The research adopts a quantitative approach with a correlational design to analyze the relationship between coping mechanisms and stress levels. Key findings indicate a diverse range of coping capabilities among students, with a majority scoring medium on the Problem-Focused Coping scale. However, a significant minority demonstrates high coping abilities, suggesting variable stress management skills as per Lazarus and Folkman’s transactional model. Alarmingly, 63% of the participants scored high in the Academic Stress category, underlining the prevalent stress challenges faced by students. Statistical analysis reveals a non-normal distribution of both coping and stress levels, hinting at unique stressors in the university environment. A significant negative correlation between Problem-Focused Coping and Academic Stress, as shown by Spearman’s rho results, supports the hypothesis that effective coping strategies can alleviate stress. The study contributes to the existing literature on stress management in academic settings by highlighting the protective role of Problem-Focused Coping against Academic Stress. It underscores the importance of developing robust coping strategies to aid students in managing academic pressures, particularly during critical phases like thesis writing. The findings also suggest the potential for interventions to enhance Problem-Focused Coping strategies, thereby supporting student well-being and academic success.